2000
DOI: 10.1094/pdis.2000.84.8.871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon Rate and Host Resistance on Blast, Scald, and Yield of Upland Rice

Abstract: Blast-resistant, partially resistant, and susceptible cultivars of rice were planted in soil amended with Si at 0, 500, or 1,000 kg/ha at two locations in eastern Colombia to assess differential responses to leaf blast, neck blast, and leaf scald, and to examine the quantity and quality of grains harvested. Leaf and neck blast on partially resistant and susceptible cultivars were reduced by Si as the rate of Si was increased. Depending on the location, the level of severity of leaf and neck blast on partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 20 publications
5
53
1
6
Order By: Relevance
“…Silicon also increases the resistance of rice to abiotic stresses including chemical stresses such as salt and metal toxicity (Ma and Yamaji, 2006;Moussa, 2006). Reports on the efficacy of Si fertilizer in decreasing the incidence and severity of rice leaf diseases have continued to come from wide ranging systems of rice production, from wetland rice in the US (Datnoff et al, 1991) and China (Ning et al, 2014), to upland rice in Colombia (Seebold et al, 2000) and organic rice in Thailand (Wattanapayapkul et al, 2011). Grain yield of field grown rice in Japan in a previous study was shown to respond to silicate fertilizer application when the Si in the straw fell below 5.1% (Inaizum and Yoshida, 1958).…”
Section: Introductionmentioning
confidence: 99%
“…Silicon also increases the resistance of rice to abiotic stresses including chemical stresses such as salt and metal toxicity (Ma and Yamaji, 2006;Moussa, 2006). Reports on the efficacy of Si fertilizer in decreasing the incidence and severity of rice leaf diseases have continued to come from wide ranging systems of rice production, from wetland rice in the US (Datnoff et al, 1991) and China (Ning et al, 2014), to upland rice in Colombia (Seebold et al, 2000) and organic rice in Thailand (Wattanapayapkul et al, 2011). Grain yield of field grown rice in Japan in a previous study was shown to respond to silicate fertilizer application when the Si in the straw fell below 5.1% (Inaizum and Yoshida, 1958).…”
Section: Introductionmentioning
confidence: 99%
“…Devido à limitação do emprego de cultivares resistentes, bem como aos aspectos econômicos e ambientais negativos associados ao controle químico, pesquisas têm se voltado para a busca de novas tecnologias. O uso de extratos vegetais (Harish et al, 2008), da aplicação de variadas formas de silício (Seebold et al, 2000;Rodrigues et al, 2003) e de agentes de biocontrole (Vidhyasekaran et al, 1997;Vidhyasekaran et al, 2001) estão entre as possibilidades estudadas.…”
Section: Introductionunclassified
“…Some economically important diseases in rice such as blast (Magnaporthe grisea (Hebert) Barr), brown spot (Cochliobolus miyabeanus (Ito & Kuribayashi in Ito) Drechs ex Dastur), stem rot (Magnaporthe salvinii Catt. ), scald (Monographella albescens Theum), and grain discoloration have been reduced by silicon fertilization (Elawad and Green, 1979;Datnoff et al, 1991Datnoff et al, , 1992Datnoff et al, , 1997Deren et al, 1994;Seebold et al, 2000Seebold et al, , 2001Kornd . orfer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%